A Longitudinal Study of the Bidirectional Relationship Between Social Support and Posttraumatic Stress Following a Natural Disaster. Issue 3 (10th May 2016) - Platt, Jonathan M.; Lowe, Sarah R.; Galea, Sandro; Norris, Fran H.; Koenen, Karestan C.
Abstract: There is ample evidence that social support is protective against posttraumatic stress (PTS) symptoms through social causation processes. It is also likely that PTS is associated with decreased social support through social selection processes. Few studies, however, have examined the longitudinal and bidirectional associations between social support and PTS in a postdisaster context, and whether such associations vary by type of support (e.g., emotional, informational, or tangible). We examined these relationships using Galveston Bay Recovery Study data. Participants ( N = 658) were interviewed 2–6 months (W1), 5–9 months (W2), and 14–19 months (W3) after Hurricane Ike in 2008. Longitudinal relationships between each support type and PTS were examined in cross‐lagged models. W1 emotional support was negatively associated with W2 PTS (Estimate = –.13, p = .007), consistent with social causation. W1 PTS was negatively associated with W2 emotional support (Estimate = –.14, p = .019), consistent with social selection. In contrast, pathways were nonsignificant at subsequent waves and for informational and tangible support. Results suggested that postdisaster social causation and selection were limited to emotional support and diminish over time. Based on these findings, postdisaster services should emphasize restoring supportive social connections to minimize the psychiatric consequences of disaster, especially among those with prior evidence of distress.